Application Of Supplementary Penalty As A Substitute For Money In Cases Of Corruption Criminal Proceedings - Muammar, Muammar; Meldandy, Maulana (Fakultas Hukum Universitas Widya Mataram, 2022)
Abstract The determination of additional punishment in the form of